2018
DOI: 10.1007/s11274-018-2542-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and engineering alcohol-tolerant bacteria using OMICS technology

Abstract: Microbes are capable of producing alcohols, making them an important source of alternative energy that can replace fossil fuels. However, these alcohols can be toxic to the microbes themselves, retaring or inhibiting cell growth and decreasing the production yield. One solution is improving the alcohol tolerance of such alcohol-producing organisms. Advances in omics technologies, including transcriptomic, proteomic, metabolomic, and genomic technologies, have helped us understand the complex mechanisms underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 93 publications
0
26
0
Order By: Relevance
“…Finally, adaptive laboratory evolution (ALE) can help improve the tolerance of microbes to butanol. ALE is a powerful technique in which a microorganism is cultivated continuously for several generations, improving its fitness in a response to a certain condition (selective pressure) by natural selection (Horinouchi, Maeda, & Furusawa, 2018). The subsequent whole-genome sequencing of the adapted strains can identify the mutations associated with butanol's tolerance.…”
Section: Improvement Of E Coli Tolerance To Butanolmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, adaptive laboratory evolution (ALE) can help improve the tolerance of microbes to butanol. ALE is a powerful technique in which a microorganism is cultivated continuously for several generations, improving its fitness in a response to a certain condition (selective pressure) by natural selection (Horinouchi, Maeda, & Furusawa, 2018). The subsequent whole-genome sequencing of the adapted strains can identify the mutations associated with butanol's tolerance.…”
Section: Improvement Of E Coli Tolerance To Butanolmentioning
confidence: 99%
“…The subsequent whole-genome sequencing of the adapted strains can identify the mutations associated with butanol's tolerance. Further integration of "omics" technology can help to unravel the regulatory and metabolic mechanisms associated with butanol tolerance (Horinouchi et al, 2018). Jeong et al (2017) have evolved a E. coli strain able to tolerate 1.3% (v/v) butanol.…”
Section: Improvement Of E Coli Tolerance To Butanolmentioning
confidence: 99%
“…Escherichia coli expresses 304 TFs (Perez-Rueda et al, 2015), though only a few have been reported to regulate butanol tolerance-related genes (Reyes et al, 2012;Horinouchi et al, 2018). Furthermore, the corresponding genes regulated by these TFs and the associated regulatory mechanism have not yet been clarified (Aquino et al, 2017), limiting the improvement of butanol-tolerant chassis strains using a rational-design engineering strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Some stand-alone SARPs (e.g.,t he large SARP AfsR) globally control secondary metabolism and morphological development. [31,32] Thus SARP gene activation can influence the productiono fm ultiple secondary metabolites.…”
Section: Introductionmentioning
confidence: 99%